2022
DOI: 10.1099/jgv.0.001718
|View full text |Cite
|
Sign up to set email alerts
|

First isolation and genomic characterization of bovine parechovirus from faecal samples of cattle in Japan

Abstract: A novel picornavirus was isolated from the faeces of a diarrhoeic cow using MA-104 cells at the third blind passage. This virus, named Den1/2021/JPN, was completely sequenced using total RNA from the cell culture supernatant by deep sequencing. The genome of Den1/2021/JPN had a standard picornavirus genome organisation with conserved picornaviral motifs. The 5′ untranslated region harboured a type-II internal ribosomal entry site. Den1/2021/JPN was most closely related to a bovine parechovirus (Bo_ParV) named … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Our qRT-PCR method for Bo_ParV detection could detect Bo_ParV in 10 (6.3%) out of 158 bovine fecal samples. In our previous study, no Bo_ParV positive samples were detected in 46 bovine fecal samples, probably because of the small sample size, sampling area, or year of specimen collection[2]. Kawasaki et al reported that parechovirus infections were detected in 944 of 8284 cow samples from the digestive, lymphatic, and central nervous systems in the SRA and did not observe a significant association between the viral infections and the presence or absence of symptoms[1].However, detailed epidemiological data, such as country, year of sample collection, and age of cows, were not included in their results.…”
mentioning
confidence: 78%
See 1 more Smart Citation
“…Our qRT-PCR method for Bo_ParV detection could detect Bo_ParV in 10 (6.3%) out of 158 bovine fecal samples. In our previous study, no Bo_ParV positive samples were detected in 46 bovine fecal samples, probably because of the small sample size, sampling area, or year of specimen collection[2]. Kawasaki et al reported that parechovirus infections were detected in 944 of 8284 cow samples from the digestive, lymphatic, and central nervous systems in the SRA and did not observe a significant association between the viral infections and the presence or absence of symptoms[1].However, detailed epidemiological data, such as country, year of sample collection, and age of cows, were not included in their results.…”
mentioning
confidence: 78%
“…Bovine parechovirus (Bo_ParV) sequences were firstly identified from the NCBI Sequence Read Archive (SRA), which is a public database of accumulated metagenomic libraries, and a nearly complete Bo_ParV sequence (Bo_ParV/2018/4/KOR) was assembled from the sequence reads from the lower digestive tract of a cow collected in South Korea in 2018 [1]. The first Bo_ParV was isolated in our laboratory in 2021 using cell culture from a bovine fecal sample that was positive for group C rotavirus [2]. This virus, Bo_ParV/Den1/2021/JPN (Den1/2021/JPN), and Bo_ParV/2018/4/KOR (2018/4/KOR) shared sequence homology with each other and were related to parechoviruses, especially the falcon parechovirus (KY645497) belonging to the Parechovirus E within the family Picornaviridae.…”
mentioning
confidence: 99%